Susceptibility assessment of geological hazards in Shenzhen Town, Ninghai county based on the APH-CF model - Han, Shuai; Li, Ran; Hui, Shujun; Sun, Qiang; Zhang, Taili (Frontiers in Earth Science, 2024)
IntroductionThis work employs a coupled evaluation model that integrates deterministic coefficients with the Analytic Hierarchy Process to conduct a comprehensive assessment of geological disaster susceptibility in Shenzhen Town, Ninghai County.MethodsCascading geological disasters induced by typhoons and rainfall in the southeast coastal area of China are a major concern and cause huge losses of life and property every year. To effectively prevent and mitigate such disasters, it is necessary to evaluate the susceptibility of geological disasters. Taking geological disasters in Shenzhen Town, Ninghai County as the research object, eight influencing factors in terms of topographic and geomorphological conditions, engineering geological conditions, and human activities were selected based on the geographic information platform (GIS) in this work. The coupling model of the certainty factor model and analytic hierarchy process method was used to evaluate the susceptibility of geological hazards in the study area.ResultsThe evaluation results illustrate that the coupling model can accurately and objectively assess the susceptibility of geological hazards in this region, with a high evaluation accuracy of 80.8%. The susceptibility is greatly affected by slope, stratigraphic lithology, and human activities. The areas with extraordinarily high and high susceptibility were identified in the northwestern part of the study, where the ignimbrite is exposed in the steep topography.DiscussionThe research method provides a reference for evaluating the susceptibility of geological hazards in the southeastern coastal region of China, and the evaluation results can provide recommendations for decision-making on disaster prevention and mitigation in this region.